Dimerization as a strategy to engineer antimicrobial peptides for application against enteric bacterial pathogens of poultry - Pitchers, Kieran (2022)
This study aimed to investigate the use of phage display in discovering novel antimicrobial peptides (AMPs), and to test the effectiveness of improving AMP activity by dimerization. AMPs are an emerging avenue of research showing potential to circumvent the antibiotic resistance crisis that is developing. These peptides offer an alternative therapeutic, one that can be used to replace/supplement current antimicrobial therapies. Characterisation studies using both standardised techniques such as broth microdilution, and others identified in the literature were used to investigate a panel of AMPs discovered by bioinformatic analysis of a phage display library. Recombinant methods were then attempted to express dimeric forms of AMPs in E. coli and inverse PCR used to insert both known AMP sequences and libraries of randomised sequences into plasmids for expression for antimicrobial susceptibility testing. Finally commercially synthesised dimeric AMPs were tested in mixed culture models and by PMA-based qPCR to investigate their activity in more realistic matrices. Characterisation studies discovered five novel AMPs with activity as low as 8 mg L-1, but it was clearly evidenced that the antimicrobial activity of these peptides is matrix-dependent, and agar-based assays are not appropriate for AMP screening. Investigations into recombinant production of AMPs highlighted some of the difficulties in expressing small, potentially toxic peptides. By conjugating the phage-derived AMPs with the potent AMP C-BF, robust and selective killing of pathogenic E. coli serotypes could be achieved within mixed cultures. Even in highly dense cultures, selectivity was retained thereby suggesting that the AMPs identified, and improved upon, here have potential for therapeutic use within poultry farming but more research into their effectiveness is needed.